Whistleblowing Phenomenon: Exploration of Instrumental Climate and Organizational Commitment Aspects - Rohma, Frida Fanani; Fatiha, Aliya Tiara; Arianti, Livia; Fadhilah, Nur (Jurnal Akuntansi, Manajemen dan Ekonomi, 2023)
This study aims to explore the role of instrumental climate and organizational commitment in explaining the phenomenon of whistleblowing. The massive fraud scandals requires an effective fraud disclosure system. However, individual tendencies to commit fraud are still limited. Thus, in depth this research will explore aspects of the role of instrumental climate and organizational commitment in the process of whistleblowing in organizations. This study uses a qualitative method with a case study approach and an interpretive paradigm. This study uses a trading company as a research site. The findings of this study provide an indication that a weak organizational climate is a fundamental reason for fraud to occur. Unfavorable organizational climate can cause individuals to behave dysfunctionally. The decrease in organizational commitment causes rationalization which causes dysfunctional behavior to be considered as a reasonable activity to do. Rationalization of dysfunctional behavior triggers individual reluctance to disclose fraud.